Bebida láctea fermentada com cultura probiótica adicionada de semente de chia (Salvia hispanica L.) - Zerbielli, Kleber Marcos (2014)
The aim of this study was to develop a fermented dairy beverage made with 60% milk, 32% whey and 8% sugar, using probiotic microorganisms. Three formulations, with 1% (A), 3% (B) and 5% chia seed (Salvia hispanica L.) have been developed. Physico-chemical analyzes on standard formulation and the formulations A, B and C for 0, 7 and 14 days were made; sensory analysis in formulations A, B, and C for times 0, 7 and 14 days and microbiological evaluation The moisture content of the three formulations showed a significant difference at 0 and 7 days of storage (p <0.05). Contents of ash, protein, lipids and viscosity increased significantly as it increased the proportion of chia. A gradual reduction of pH and increase in acidity due to the storage time of the beverage was observed. The product has obtained good acceptability, but a decrease was observed in the global acceptability and intention of consumption during the storage period. The probiotic bacteria count was reduced by about 1 log cycle per week. The preferred formulation of the ranking preference test was the formulation A.